Post-prandial blood glucose of four cultivars of date palm (Phoenix dactylifera) in healthy subjects (El-Wahat Journal for Research and Studies, 2025)
This study was designed to determine the post-prandial bloodglucose of four commonly used cultivars of dates (“Ghars"; "DegletNour" ; "Degla Beida"; "Addela") in healthy subjects and their effects onglycemic index. This research also aims to explore the possibility ofconsumption of these cultivars of dates by obese and diabetics. Thesecultivars were chosen on the basis of their consumption enhanced by thelocal population.Composition analysis was carried out for four types of dates. Theweights of the flesh of the date’s equivalent to 50 g of availablecarbohydrates (7 to 8 dates) were calculated. The study subjects weretwenty eight volunteers (non-diabetic) with a mean age of 22.14 ± 0.134years. Each volunteer was tested on five separate days with 50 g ofglucose (reference food) and 50 g equivalent of available carbohydratesfrom the 4 cultivars of date. Capillary glucose was measured involunteers at 0, 15, 30, 45, 60, 90 and 120 min. The post-prandialresponse was recorded by using MATLAB program. The glycemic indexwas determined as ratios of the incremental areas under the responsecurves for the dates compared to glucose. Mean glycemic index of thedates were 43.27±14.05, 52.22±9.82, 53.95±23 and 42.11±14.05 forGhars, Deglet Nour, Degla Beida and Addela, respectively. There werestatistically significant differences in the GI between the four cultivars ofdates. The results show low glycemic indices for the four types of datesincluded in the study and that their consumption by healthy individualsdoes not result in significant postprandial glucose excursions. Thesefindings point to the potential benefits of dates for diabetic subjects whenused in a healthy balanced diet.Key words: Dates; Glycemic Index, diabetes, obesity, Algeria